Tribolium castaneum defensin 1 kills Moraxella catarrhalis in an in vitro infection model but does not harm commensal bacteria - Bertrams, Wilhelm; Lindhauer, Nora S.; Rieke, Marie Christin; Paas, Anne; Hoffmann, Kerstin; Greene, Brandon; Visekruna, Alexander; Vilcinskas, Andreas; Seidel, Kerstin; Schmeck, Bernd (Virulence, 2021)
Moraxella catarrhalis is a bacterial pathogen that causes respiratory tract infections in humans. The increasing prevalence of antibiotic-resistant M. catarrhalis strains has created a demand for alternative treatment options. We therefore tested 23 insect antimicrobial peptides (AMPs) for their activity against M. catarrhalis in a human in vitro infection model with primary macrophages, and against commensal bacteria. Effects on bacterial growth were determined by colony counting and growth curve analysis. The inflammatory macrophage response was characterized by qPCR and multiplex ELISA. Eleven of the AMPs were active against M. catarrhalis. Defensin 1 from the red flour beetle Tribolium castaneum significantly inhibited bacterial growth and reduced the number of colony forming units. This AMP also showed antibacterial activity in the in vitro infection model, reducing cytokine expression and release by macrophages. Defensin 1 had no effect on the commensal bacteria Escherichia coli and Enterococcus faecalis. However, sarcotoxin 1 C from the green bottle fly Lucilia sericata was active against M. catarrhalis and E. coli, but not against E. faecalis. The ability of T. castaneum defensin 1 to inhibit M. catarrhalis but not selected commensal bacteria, and the absence of cytotoxic or inflammatory effects against human blood-derived macrophages, suggests this AMP may be suitable for development as a new therapeutic lead against antibiotic-resistant M. catarrhalis.